All-Solution-Processed Quantum Dot Electrical Double-Layer Transistors Enhanced by Surface Charges of Ti3C2Tx MXene Contacts - Kim, Hyunho; Nugraha, Mohamad I; Guan, Xinwei; Wang, Zhenwei; Hota, Mrinal K; Xu, Xiangming; Wu, Tom; Baran, Derya; Anthopoulos, Thomas D; Alshareef, Husam N (ACS nano, 2021)
Fully solution-processed, large-area, electrical double-layer transistors (EDLTs) are presented by employing lead sulfide (PbS) colloidal quantum dots (CQDs) as active channels and Ti3C2Tx MXene as electrical contacts (including gate, source, and drain). The MXene contacts are successfully patterned by standard photolithography and plasma-etch techniques and integrated with CQD films. The large surface area of CQD film channels is effectively gated by ionic gel, resulting in high performance EDLT devices. A large electron saturation mobility of 3.32 cm2 V-1 s-1 and current modulation of 1.87 × 104 operating at low driving gate voltage range of 1.25 V with negligible hysteresis are achieved. The relatively low work function of Ti3C2Tx MXene (4.42 eV) compared to vacuum-evaporated noble metals such as Au and Pt makes them a suitable contact material for n-type transport in iodide-capped PbS CQD films with a LUMO level of ∼4.14 eV. Moreover, we demonstrate that the negative surface charges of MXene enhance the accumulation of cations at lower gate bias, achieving a threshold voltage as low as 0.36 V. The current results suggest a promising potential of MXene electrical contacts by exploiting their negative surface charges.Fully solution-processed, large-area, electrical double-layer transistors (EDLTs) are presented by employing lead sulfide (PbS) colloidal quantum dots (CQDs) as active channels and Ti3C2Tx MXene as electrical contacts (including gate, source, and drain). The MXene contacts are successfully patterned by standard photolithography and plasma-etch techniques and integrated with CQD films. The large surface area of CQD film channels is effectively gated by ionic gel, resulting in high performance EDLT devices. A large electron saturation mobility of 3.32 cm2 V-1 s-1 and current modulation of 1.87 × 104 operating at low driving gate voltage range of 1.25 V with negligible hysteresis are achieved. The relatively low work function of Ti3C2Tx MXene (4.42 eV) compared to vacuum-evaporated noble metals such as Au and Pt makes them a suitable contact material for n-type transport in iodide-capped PbS CQD films with a LUMO level of ∼4.14 eV. Moreover, we demonstrate that the negative surface charges of MXene enhance the accumulation of cations at lower gate bias, achieving a threshold voltage as low as 0.36 V. The current results suggest a promising potential of MXene electrical contacts by exploiting their negative surface charges.